The Local Impacts of World Bank Development Projects Near Sites of Conservation Significance. (September 2018) - Buchanan, Graeme M.; Parks, Bradley C.; Donald, Paul F.; O'Donnell, Brian F.; Runfola, Daniel; Swaddle, John P.; Tracewski, Łukasz; Butchart, Stuart H. M.
We evaluated the local impacts of World Bank development projects on sites of recognized conservation significance (Important Bird and Biodiversity Areas [IBAs]) using tree cover change data and in situ state, pressure, and response monitoring data. IBAs adjacent to World Bank project locations and a matched set of IBAs distant from World Bank project locations had similar rates of tree loss and similar in situ measurements of conservation outcomes. Thus, we did not detect any significant net negative impacts of World Bank projects on tree cover or conservation outcomes. These results are encouraging because 89% of World Bank projects that are close to IBAs are environmentally sensitive projects (so-called Category A and Category B projects) subjected to the organization's most stringent safeguards. However, the limitations of our evaluation design do not allow us to rule out the possibility that World Bank projects had positive or negative effects that were undetectable.